What is the solution to the equation 1−5(x3+x2)=-5x2−4(x3+2)?
When you write these Shaniab you should use the 'hat' to indicate exponents. :)
I would like you to try and do it yourself Shaniab
Just remember that the minus sign belongs to the number that follows it.
I have added stuff that might help you a bit.
Now can you give it a go?
1 -5(x^3+x^2) = -5x^2 -4(x^3 +2)
1 -5x^3 -5x^2 = -5x^2 -4x^3 -8
1 -5x^3 = -4x^3 - 8
1 +8 = -4x^3 + 5x^3
9 = x^3
Your answer appears to bre perfect Sasini. Thank you
Shaniab, It is important that when you show woking for your answers that you only ever put one equal sign per line.
It is too hard to think it through otherwise :)